2020
DOI: 10.4103/jfmpc.jfmpc_953_19
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of bariatric surgery among adult Saudi community, Saudi Arabia, 2019

Abstract: The prevalence of overweight and obesity is higher in developed countries than in developing countries of all ages (data from 2013). This study is aimed at assessing the knowledge and attitudes of people in Saudi Arabia toward bariatric surgery. To do this, the specific objectives sought to determine the satisfaction of people who underwent bariatric surgery and to determine the importance of bariatric surgery among the community. Methods: The study is a cross-sectional, community-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
3
7
0
Order By: Relevance
“…The findings of this study are that there is widespread knowledge of risk factors for obesity among citizens in Saudi Arabia; it agrees with [ 20 ]. The participants' knowledge of obesity risk factors was generally high (95.5%).…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study are that there is widespread knowledge of risk factors for obesity among citizens in Saudi Arabia; it agrees with [ 20 ]. The participants' knowledge of obesity risk factors was generally high (95.5%).…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the study reveal that a high majority of the enrolled family medicine physicians knew that diabetes mellitus can be controlled through bariatric surgery, ideal weight loss can be achieved through bariatric surgery, and surgical treatment of obesity and metabolic diseases is safe and reliable, they would recommend bariatric surgery to a family member or a friend with class III obesity. These findings are referred to the increasing and successful cases in Saudi Arabia and positive outcomes demonstrated by the positive perception that are reported in different studies, such as Alghutayghit et al [23] and Alfadhel et al [24] who reported an increased in-public and healthcare workers' perceptions towards bariatric surgeries.…”
Section: Discussionmentioning
confidence: 71%
“…A total of 3131 people were surveyed or interviewed, of which 64% were women. Across three studies, 26% of respondents thought that bariatric surgery was primarily a cosmetic procedure 88,91,92 . In the largest cohort, 40% said they would not want bariatric surgery, although the mean BMI in this cohort was only 28 kg/m 2 88 .…”
Section: Resultsmentioning
confidence: 99%
“…Five cross‐sectional studies were identified looking at public perceptions of obesity and bariatric surgery in SA 88–92 . A total of 3131 people were surveyed or interviewed, of which 64% were women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation